(untitled) - Brett, Jeanne M. (San Francisco, 2001)
This is an excellent book for mediators interested in cultural diversity and negotiation
Keywords: Negotiation in business,Negotiation,Decision making,Conflict management,Đàm phán trong kinh doanh,Nghệ thuật đàm phán